Comparative Effects of Shuttle Run and Zigzag Run Training on Physical Performance among School-Level Soccer Players - Aramana, Vasco Tein; Hidayat, Syarif; Ariani, Luh Putu Tuti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
Soccer requires players to perform repeated high-intensity actions, rapid changes of direction, and sustained physical effort throughout a match. This study examined the comparative effects of shuttle run and zigzag run training on two specific components of physical performance, namely agility and endurance, among school-level soccer players. The research used a two-group pretest–posttest experimental design. A total of 100 students from SMPN 2 Larantuka were divided into two training groups: 50 students performed shuttle run training and 50 students performed zigzag run training on a sand surface. Agility was assessed using a time-based agility running test, in which shorter completion time indicated better performance, while endurance was measured using the multistage beep test and expressed as level achievement. The results showed that both training methods significantly improved agility and endurance after the intervention. The shuttle run group improved agility from 19.63 to 17.24 seconds and endurance from 4.86 to 7.54 levels, whereas the zigzag run group improved agility from 19.59 to 16.85 seconds and endurance from 4.79 to 7.05 levels. The comparison of gain scores indicated that zigzag run training produced greater improvement in agility, with a mean gain of 2.74 seconds compared with 2.39 seconds in the shuttle run group, because it emphasized multidirectional movement, body control, and repeated change-of-direction actions. In contrast, shuttle run training produced greater improvement in endurance, with a mean gain of 2.68 levels compared with 2.26 levels in the zigzag run group, because it required repeated high-intensity running, acceleration, deceleration, and short recovery cycles that stimulated cardiorespiratory adaptation. These findings indicate that both exercises are effective but have different dominant training effects. Therefore, zigzag run training is more suitable for agility development, whereas shuttle run training is more appropriate for endurance improvement in school-level soccer conditioning programs. Keywords: shuttle run; zigzag run; agility; endurance; soccer training; sand training; physical performance